의과대학생에서 스트레스 대처방식과 사회적 지지가 스트레스의 지각에 미치는 영향 - 이이레; 김민경; 김혜원; Lee, I Re; Kim, Min-Kyeong; Kim, Hae Won (Anxiety and mood, 2021)
Objective : We aimed to examine the demographic factors and personal resources that affect medical students' perceived stress. In particular, the extent to which coping strategies and social support influenced perceived stress was investigated. Methods : A total of 321 medical students, which consisted of 116 first-year students, 100 second-year students, and 105 third-year students, participated in the present study. The levels of perceived stress, coping style, and perceived social support were measured by the perceived stress scale, the ways of coping scale, and the multi-dimensional scale of perceived social support, respectively. The influence of coping style and social support on perceived stress was examined by multiple linear regression, after controlling for age, sex, grade, and medical school entrance type. Results : The perceived stress level was significantly different between undergraduate-entry and graduate-entry medical students (18.39 vs. 16.38, t=2.625, p=0.009). Other sociodemographic factors did not affect the extent to which medical students experienced stress. The multiple regression model was significant (p<0.001), and active problem-focused coping (p<0.001) and social support from friends (p=0.003) were associated with a lower level of perceived stress. Conclusion : Our results suggest that problem-focused strategies and supportive relationships with friends may play a role in reducing medical students' stress levels. These findings have implications for teaching students how to approach stressful situations and encouraging students to build communities among themselves may help students manage stress during medical school effectively.